Implikatur Wacana Iklan Rokok dan Pemanfaatannya dalam Pembelajaran Berbahasa - Djokowidodo, Agustinus (Widya Warta, 2021)
Every company that produces goods and services will undoubtedly be able to sell its product to the public. Many companies introduce their products using advertising facilities. One of them is cigarette advertising. This research was limited to the description of the cigarette advertising discourse to obtain a more in-depth picture of the types of speech, the implicature in the cigarette advertisement discourse, and to gain insight into the use of this implicature in the language learning process. The data in this study was the discourse in cigarette advertisements on television recorded from April to August 2018, which were then transcribed into written sentences. The results showed that the discourse on cigarette advertisements often seemed incompatible with the advertised cigarette products. All cigarette product advertisements with symbolic languages invited the audience to dream, drift and imagine a pleasure or enjoyment that ultimately wanted to consume the product offered. The sentence used was an implicature utterance. The implicature contained in the cigarette advertisement discourse consisted of two kinds, namely conventional implicature, and non-conventional implicature. Of the two types of implicatures, only conventional ones could be used as a means of language learning, especially in terms of language sensitivity through satire, the substitution of harsh words.